IN A CLASSROOM CONTEXT, STUDENTS WHO ARE GIVEN CONCISE EXPLANATIONS ARE MORE LIKELY TO COMPREHEND THE MATERIAL (Journal of Science-Innovative Research in Uzbekistan, 2023)
Giving students concise explanations is essential in the classroom to ensure  they understand the material. When it comes to generalizing, students' logical  thinking is strengthened and provides guidance through inductive judgment.  Regarding explanations, Leinhardt distinguished between disciplinary and  instructional forms of teaching. He argues that instructional explanations aim to  make concepts, procedures, events, ideas, and classes of problems clearer in order  to assist students in comprehending, learning, and applying information in a flexible manner.